A constructivism-based training course for hospitality and tourism instructors in Vietnam to improve their self-confidence in synchronous online teaching. Issue 3 (16th August 2021) - Luong, Thanh-Thao; Kim, Eunyoung
Abstract : Purpose: As Vietnam needs to shift from physical to virtual classrooms owing to the coronavirus disease 2019 (COVID-19) pandemic, this study aims to propose and evaluate a constructivist training course designed to improve instructors' self-confidence in conducting synchronous online teaching by helping them develop the skills required for such. Design/methodology/approach: A total of 67 in-service instructors in various hospitality and tourism institutions in Vietnam participated in the proposed course. Constructivist approaches were adopted to design learning activities. Delivered via Blackboard Collaborate's classroom version, the course aims at enhancing instructors' self-confidence in the knowledge and skills required for synchronous online teaching: developing online presence, planning lessons, handling technology, adapting to learners' preferences and classroom management. Using qualitative and quantitative analyses, this paper evaluated the proposed course by comparing participants' levels of self-confidence in conducting synchronous online teaching before and after the training. Findings: The results show that participants' self-confidence was enhanced after the course. To improve the course, however, more time should be allotted for practice sessions where participants can pedagogically and technologically familiarize themselves with online teaching tools. Originality/value: By translating constructivism into online pedagogy, this study provided empirical evidence of how a teachers' training program was designed and implemented to meet the need to shift from real-life to real-time classrooms in Vietnam during the COVID-19 pandemic. It also contributes to the growing literature on methods of improving instructors' readiness in synchronous online teaching.